2021
DOI: 10.7554/elife.66747
|View full text |Cite
|
Sign up to set email alerts
|

Mapping single-cell atlases throughout Metazoa unravels cell type evolution

Abstract: Comparing single-cell transcriptomic atlases from diverse organisms can elucidate the origins of cellular diversity and assist the annotation of new cell atlases. Yet, comparison between distant relatives is hindered by complex gene histories and diversifications in expression programs. Previously, we introduced the self-assembling manifold (SAM) algorithm to robustly reconstruct manifolds from single-cell data (Tarashansky et al., 2019). Here, we build on SAM to map cell atlas manifolds across species. This n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 76 publications
2
133
0
Order By: Relevance
“…We compared our cell-type alignments between zebrafish versus frog to a recent study 110 that also sought to align the same datasets. We could find consistent alignments for 35 of 46 pairs of cell types that they identified (Supplementary Table 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…We compared our cell-type alignments between zebrafish versus frog to a recent study 110 that also sought to align the same datasets. We could find consistent alignments for 35 of 46 pairs of cell types that they identified (Supplementary Table 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…This view does not prevent establishing evolutionary lineages of homologous cell types within particular taxonomical units such as classes, subclasses, orders, families, and genera. The cell-lineage-specific homologies across phyla are still a challenge (Tarashansky et al, 2020 ).…”
Section: Postulates Of the Polygeny Hypothesismentioning
confidence: 99%
“…But, no criteria for cell-specific homologies across phyla have been established and experimentally validated. Some approaches are suggested (Tarashansky et al, 2020 ), but true homology can only be found with multiple cross-validated criteria, including identifying potential continuity of homologs tracing intermedial species. Here, the lack of required comparative data from “minor” phyla and classes is a significant bottleneck.…”
Section: Questions and Prospective For Exprerimental Validationmentioning
confidence: 99%
“…By defining a set of homologous genes across species, cross-species comparison of gene expression can be achieved to study problems such as the expression pattern of core genes of the cells. For closely related species, commonly used methods such as STAR can be applied to identify a set of homologous genes across species; there are also programs such as SAMap [ 56 ] to build a homologous gene set between distant species that is usually a challenge.…”
Section: Considerations When Planning a Scseq Study In Non-model Orga...mentioning
confidence: 99%